Business without borders : a strategic guide to global marketing. - DePalma, Donald A., ....- (New York : Wiley, 2002)
Ch. 1 Discovering the Eighth Continent Ch. 2 Great Expectations for Global Markets Ch. 3 Navigating the Global JourneyCh. 4 Deciding Which Markets Matter Ch. 5 The Laws of the Eighth Continent